Política exterior de Costa Rica hacia centroamérica: perspectiva política y económica (1990-2013) - Madrigal Rodríguez, Jean Paul (2013)
This paper studies the relationship between Costa Rica and the CentralAmerican region, taking into account the influence of the international environment.For this, it analyzes the period from 1990 —a milestone in the historical development of the international system— up to the present. The author begins with the idea that the relationship between Costa Rica and the region can be understood as a paradox between political skepticism and economic activism; at the same time, he shows how this country has achieved convergence between its historic isolationism and the need to remain integrated into the region